Hollow fiber nanofiltration membrane, method for preparing the same, and use thereof

CN122230556BActive Publication Date: 2026-08-28FOSHAN CHANCHENG WATER SUPPLY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610678492.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-18
Publication Date
2026-08-28
Estimated Expiration
2046-05-18

AI Technical Summary

Technical Problem

然而现有聚醚砜在实际应用中容易受到污染,尤其是在长期运行过程中,膜表面的有机、无机及生物污染会导致膜通量迅速衰减,进而增加系统的运行成本和维护难度

Benefits of technology

本发明首先以聚醚砜和磺化聚醚砜构建中空纤维基膜,在保证膜体机械强度和耐化学稳定性的同时,提高了基膜的亲水性和表面荷电特性;随后通过多巴胺层在中空纤维基膜内表面构建稳定的黏附中间层,并在其表面接枝两性离子和亲水聚合物,形成超亲水抗污染刷层,从而有效降低有机污染物、无机污染物及微生物在膜表面的沉积倾向;最后在刷层表面固定光催化材料和吸附材料,构建光催化/吸附复合功能层,使所得中空纤维纳滤膜兼具抗污染、自清洁和目标污染物去除功能。由此,所制备的中空纤维纳滤膜能够有效延缓膜通量衰减,减少清洗频次和更换频率,降低运行能耗,并在复杂水体处理中保持较好的分离性能和运行稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122230556B_ABST
    Figure CN122230556B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of water treatment, and discloses a hollow fiber nanofiltration membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing polyether sulfone, sulfonated polyether sulfone, a hydrophilic auxiliary agent and a first solvent to prepare a casting solution, and then obtaining a hollow fiber base film by using a phase inversion method; (2) constructing a dopamine layer in the inner cavity of the hollow fiber base film, and grafting zwitterions and hydrophilic polymers through a polymerization reaction to form a brush layer; and (3) fixing a photocatalytic material and an adsorption material on the brush layer to form a photocatalysis / adsorption composite functional layer. According to the application, the prepared modified hollow fiber nanofiltration membrane can effectively improve the anti-pollution performance, delay the membrane flux attenuation, reduce the cleaning and replacement frequency, reduce the energy consumption, and maintain the efficient water treatment effect in complex water bodies, so that the application prospect of the modified hollow fiber nanofiltration membrane is wide in the water treatment fields such as drinking water, municipal water or sewage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment technology, and in particular to a hollow fiber nanofiltration membrane, its preparation method, and its application. Background Technology

[0002] Currently, traditional water treatment technologies still face severe challenges in removing emerging pollutants, pathogenic microorganisms, and heavy metals from water sources, posing risks to the safety of effluent water quality. Membrane filtration technology, as a novel water treatment method, is gradually becoming a widely adopted technology due to its advantages such as small footprint, ease of operation, and lack of the generation of new harmful byproducts. Compared to traditional organic membranes, polyethersulfone hollow fiber nanofiltration membranes possess higher mechanical strength, better chemical corrosion resistance, and washability, and can effectively remove dissolved organic matter, salts, and micro-pollutants from water. However, existing polyethersulfone membranes are susceptible to fouling in practical applications, especially during long-term operation. Organic, inorganic, and biological fouling on the membrane surface leads to a rapid decline in membrane flux, thereby increasing system operating costs and maintenance difficulty. Therefore, the market urgently needs a hollow fiber nanofiltration membrane material with excellent anti-fouling and antibacterial properties and the ability to operate stably for extended periods to address the increasingly serious water quality safety issues. Summary of the Invention

[0003] The technical problem to be solved by the present invention is to provide a hollow fiber nanofiltration membrane, its preparation method and application, which can maintain high flux while having excellent antifouling ability and improve the retention effect of pollutants and dissolved organic matter.

[0004] To address the aforementioned technical problems, the first aspect of this invention provides a method for preparing a hollow fiber nanofiltration membrane, comprising the following steps: (1) A casting solution was prepared by mixing polyethersulfone, sulfonated polyethersulfone, hydrophilic additives and a first solvent, and then a hollow fiber base membrane was obtained by phase inversion method; (2) A dopamine layer is constructed in the inner cavity of the hollow fiber base membrane, and a zwitterion and hydrophilic polymer are grafted through a polymerization reaction to form a brush layer; (3) Fix photocatalytic material and adsorbent material on the brush layer to form a photocatalytic / adsorption composite functional layer.

[0005] As an improvement to the above scheme, in step (1), the total solid content of polyethersulfone and sulfonated polyethersulfone in the casting solution is 10wt%-35wt%, wherein the sulfonated polyethersulfone is 5wt%-40wt% of the total mass of polyethersulfone and sulfonated polyethersulfone.

[0006] As an improvement to the above scheme, in step (1), the amount of the hydrophilic auxiliary agent added is 1wt%-15wt% of the first solvent; The hydrophilic additive is selected from one or more of polyethylene glycol, polyvinyl alcohol, and polyvinylpyrrolidone; The casting solution also includes a pore-forming agent, and the dosage of the pore-forming agent is 0-5 wt% of the casting solution. The pore-forming agent is selected from one or more of calcium chloride, lithium chloride, and lithium carbonate.

[0007] As an improvement to the above scheme, step (2) specifically includes: (21) After wetting the hollow fiber base membrane, contact its inner cavity with dopamine buffer solution to allow dopamine to self-oxidize and deposit in the hollow fiber base membrane to form a dopamine layer; (22) The material obtained in step (21) is immersed in a mixture containing zwitterionic monomers and hydrophilic polymer monomers, and polymerized under the action of an initiator to form a brush layer.

[0008] As an improvement to the above scheme, the total mass fraction of zwitterionic monomers and hydrophilic polymer monomers added to the mixture is 1wt%-50wt%. The mass ratio of the zwitterionic monomer to the hydrophilic polymer monomer is (1-4):1. The zwitterionic monomer is selected from one or more of sulfo-beet methacrylate and carboxy-beet methacrylate; the hydrophilic polymer monomer is selected from one or more of 2-carboxyethyl methacrylate, polyethylene glycol methacrylate, and acrylamide.

[0009] As an improvement to the above scheme, step (3) specifically includes: (31) The photocatalytic material, adsorbent material, binder and second solvent are mixed to form a dispersion; (32) Wet the material obtained in step (2), and use an internal circulation process to bring the dispersion into contact with the brush layer, and deposit a photocatalytic / adsorption composite functional layer on the brush layer; (33) The material obtained in step (32) is added to a crosslinking agent to carry out a crosslinking reaction, and a photocatalytic / adsorption composite functional layer is formed on the brush layer.

[0010] As an improvement to the above scheme, in step (31), the total mass fraction of photocatalytic material and adsorbent material in the dispersion is 0.1wt%-5wt%, wherein the mass ratio of the added photocatalytic material and adsorbent material is 1:(0.5-4). The second solvent is water or an aqueous solution containing ethanol; The adhesive is selected from one or more of glutaraldehyde, carbodiimide, and polyvinyl alcohol; the dosage of the adhesive is 0.01wt%-1wt% of the dispersion. In step (32), the circulation temperature of the internal cavity circulation process is 10℃-50℃, and the circulation flow rate is 0.5mL / min-10mL / min; In step (33), the crosslinking agent is one or more of glutaraldehyde and carbodiimide; the crosslinking reaction time is 5 min to 120 min; the crosslinking agent is added in solution form; and the mass fraction of the crosslinking agent is 0.01 wt% to 2 wt%.

[0011] As an improvement to the above scheme, in step (3), the average particle size of the photocatalytic material is 10nm-500nm, and the specific surface area is 5m². 2 / g-200m 2 / g; the photocatalytic material is selected from one or more of g-C3N4, BiVO4, and Bi2WO6.

[0012] The pore size of the adsorbent material is 0.5nm-5nm, and the average particle size is 20nm-500nm; the adsorbent material is selected from one or more of β-cyclodextrin / propylene oxide crosslinks and porous aromatic polymers.

[0013] A second aspect of the present invention provides a hollow fiber nanofiltration membrane, which is prepared according to the preparation method described above.

[0014] A third aspect of the present invention provides an application of a hollow fiber nanofiltration membrane for the deep treatment of drinking water, municipal water or sewage.

[0015] Implementing this invention has the following beneficial effects: This invention first constructs a hollow fiber base membrane using polyethersulfone and sulfonated polyethersulfone, improving the hydrophilicity and surface charge characteristics of the base membrane while ensuring its mechanical strength and chemical stability. Subsequently, a stable adhesion intermediate layer is constructed on the inner surface of the hollow fiber base membrane via a dopamine layer, and zwitterionic and hydrophilic polymers are grafted onto its surface to form a superhydrophilic antifouling brush layer, effectively reducing the deposition tendency of organic pollutants, inorganic pollutants, and microorganisms on the membrane surface. Finally, photocatalytic and adsorbent materials are fixed on the brush layer surface to construct a photocatalytic / adsorption composite functional layer, giving the resulting hollow fiber nanofiltration membrane antifouling, self-cleaning, and target pollutant removal functions. Therefore, the prepared hollow fiber nanofiltration membrane can effectively delay membrane flux decay, reduce cleaning and replacement frequency, lower operating energy consumption, and maintain good separation performance and operational stability in complex water treatment. Attached Figure Description

[0016] Figure 1 This is a photograph of the hollow fiber nanofiltration membrane obtained in Example 1. Figure 2 This is a SEM image of the inner surface of the hollow fiber nanofiltration membrane obtained in Example 1; Figure 3 Here is a SEM image of the cross-section of the hollow fiber nanofiltration membrane obtained in Example 1; Figure 4 The graph shows the membrane specific flux attenuation trend of the hollow fiber nanofiltration membranes obtained in the examples and comparative examples; Figure 5 The specific flux recovery rate of the hollow fiber nanofiltration membranes obtained in the examples and comparative examples is shown in the figure. Figure 6 The images show the removal effect of hollow fiber nanofiltration membranes obtained in the examples and comparative examples on typical odor substances. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to specific embodiments.

[0018] In the description of this application, it is necessary to understand that the orientation or positional relationship indicated by terms such as "upper", "lower", "top", "bottom", "inner", and "outer" are based on the orientation or positional relationship shown in the accompanying drawings. They are intended only to facilitate the description of the present invention and to simplify the description, and are not intended to indicate or imply that the components referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the present invention.

[0019] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. The range defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range.

[0020] To address the above problems, the first aspect of this invention provides a method for preparing a hollow fiber nanofiltration membrane, comprising the following steps: (1) A casting solution was prepared by mixing polyethersulfone, sulfonated polyethersulfone, hydrophilic additives and a first solvent, and then a hollow fiber base membrane was obtained by phase inversion method; (2) A dopamine layer is constructed in the inner cavity of the hollow fiber base membrane, and a zwitterion and hydrophilic polymer are grafted through a polymerization reaction to form a brush layer; (3) Fix photocatalytic material and adsorbent material on the brush layer to form a photocatalytic / adsorption composite functional layer.

[0021] In this invention, firstly, polyethersulfone and sulfonated polyethersulfone are used as casting solutions to obtain a hollow fiber-based membrane material with good mechanical strength, corrosion resistance, and high water flux. Subsequently, an adhesion interlayer is formed on the surface of the hollow fiber-based membrane through a dopamine layer, and free radical polymerization of zwitterions and hydrophilic monomers is initiated on this layer to construct a dense, superhydrophilic, antifouling brush layer. Finally, a photocatalytic / adsorption composite functional layer is prepared on the brush layer. The resulting modified hollow fiber nanofiltration membrane can effectively improve antifouling performance, delay membrane flux decay, reduce cleaning and replacement frequency, lower energy consumption, and maintain high water treatment efficiency in complex water bodies, showing broad application prospects in drinking water, municipal water, or wastewater treatment.

[0022] Among them, the polyethersulfone / sulfonated polyethersulfone hollow fiber membrane is suitable for the treatment of drinking water, municipal water and other water bodies containing organic pollutants or trace pollutants; the constructed brush layer can reduce the irreversible adhesion of organic pollutants, bacteria and other pollutants on the membrane surface, thereby improving the membrane's antifouling ability and slowing down the membrane fouling process; the further constructed photocatalytic / adsorption composite functional layer enables the membrane to have both pollutant enrichment and removal and photoresponsive self-cleaning ability during operation. Therefore, the resulting hollow fiber nanofiltration membrane is particularly suitable for the treatment of complex water bodies containing odorous substances.

[0023] Specifically, step (1) includes; (11) Prepare a casting solution by mixing polyethersulfone, sulfonated polyethersulfone, hydrophilic additives and a first solvent; In this invention, polyethersulfone and sulfonated polyethersulfone are used synergistically as film-forming polymers in the casting solution, which is beneficial for preparing hollow fiber base films with good hydrophilicity, surface negative charge, mechanical strength and chemical stability, providing a stable substrate for the subsequent construction of surface functional layers.

[0024] Preferably, the total solids content of the polyethersulfone and sulfonated polyethersulfone is 10wt%-35wt%; more preferably 15wt%-25wt%.

[0025] Further, the sulfonated polyethersulfone comprises 5wt%-40wt% of the total mass of the polyethersulfone and the sulfonated polyethersulfone. The sulfonic acid groups in the sulfonated polyethersulfone are strongly polar groups, which can enhance the hydrophilicity of the hollow fiber membrane, thereby improving its antifouling performance, reducing cleaning and replacement frequency. Controlling the sulfonated polyethersulfone within the above range can balance the hydrophilicity, surface charge, film stability, and mechanical strength of the hollow fiber membrane. If the amount of sulfonated polyethersulfone added is too low, the improvement on membrane hydrophilicity and antifouling performance is limited; however, if the amount of sulfonated polyethersulfone added is too high, it will lead to increased viscosity of the casting solution, imbalance in the phase transformation process, and may cause uneven membrane pore structure, increased membrane brittleness, and decreased mechanical strength. More preferably, the sulfonated polyethersulfone comprises 10wt%-30wt% of the total mass of the polyethersulfone and the sulfonated polyethersulfone; more preferably, it comprises 14wt%-25wt%.

[0026] Preferably, the addition of the hydrophilic additive can improve the hydrophilicity of the hollow fiber base membrane, adjust the viscosity of the casting solution, promote the formation of pore structures, and synergistically enhance antifouling properties with sulfonated polyethersulfone. Simultaneously, the hydrophilic additive can also adjust the rheological properties of the casting solution, which is beneficial for the stable molding of the hollow fiber structure. The dosage of the hydrophilic additive is 1wt%-15wt% of the first solvent. If the dosage of the hydrophilic additive is too low, its effect on increasing the hydrophilicity of the hollow fiber base membrane and promoting the formation of pore structures will be insignificant; if the dosage of the hydrophilic additive is too high, it can easily cause the membrane pore structure to be too loose, reduce mechanical properties, and even affect spinning stability. More preferably, the dosage of the hydrophilic additive is 2wt%-10wt% of the first solvent.

[0027] Furthermore, the hydrophilic additive is selected from one or more of polyethylene glycol, polyvinyl alcohol, and polyvinylpyrrolidone.

[0028] Preferably, the first solvent is an organic solvent, which may be selected from one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and dimethyl sulfoxide.

[0029] In some specific and preferred embodiments, the casting solution also includes a pore-forming agent, which can serve as a nucleation site to regulate the pore structure and porosity of the hollow fiber membrane and improve the hydrophilicity and antifouling properties of the hollow fiber nanofiltration membrane.

[0030] Further, the amount of the pore-forming agent added is 0-5 wt% of the casting solution; more preferably, the amount of the pore-forming agent added is 0.1 wt%-2 wt% of the casting solution. Specifically, the pore-forming agent can be an inorganic salt pore-forming agent, such as calcium chloride, lithium chloride, lithium carbonate, etc.

[0031] (12) The obtained casting solution was subjected to degassing under reduced pressure, followed by aging and filtration; In this step, degassing treatment can prevent air bubbles from causing voids or breakage in the film fibers during subsequent spinning, thus affecting the mechanical strength of the base film. The subsequent aging treatment can fully stretch the molecular chains in the casting solution and reach a thermodynamic equilibrium state, which helps to improve the uniformity and stability of the casting solution, thereby ensuring that the hollow fiber base film formed during spinning has a more uniform structure and a more concentrated pore size distribution.

[0032] The pressure, temperature, and time of the degassing treatment can be adjusted appropriately based on the composition and viscosity of the casting solution. In some embodiments, the temperature of the degassing treatment is 30℃-60℃, and the time is 2h-48h; preferably, the temperature of the degassing treatment is 30℃-50℃, and the time is 8h-24h; more preferably, the temperature of the degassing treatment is 35℃-45℃, and the time is 10h-14h.

[0033] Preferably, the aging treatment is performed at a temperature of 30℃-60℃ for 8h-24h; more preferably, the aging treatment is performed at a temperature of 35℃-45℃ for 10h-18h.

[0034] Understandably, the filtration can be performed using a 0.45 μm filter membrane.

[0035] (13) The filtered casting liquid is passed into the outer channel of the hollow fiber spinneret, the inner channel is passed into the inner coagulation liquid, and finally enters the outer coagulation bath to complete the phase transformation. In this step, the ratio of the flow rate of the casting liquid to the flow rate of the internal solidification liquid is 1:(0.2-1.5); preferably 1:(0.3-1.0).

[0036] In some embodiments, the flow rate of the casting solution is 5 mL / min-20 mL / min, preferably 8 mL / min-15 mL / min. Exemplary flow rates can be 8 mL / min, 8.5 mL / min, 9 mL / min, 9.5 mL / min, 10 mL / min, 10.5 mL / min, 11 mL / min, 11.5 mL / min, 12 mL / min, 12.5 mL / min, 13 mL / min, 13.5 mL / min, 14 mL / min, 14.5 mL / min, and 15 mL / min, but are not limited thereto.

[0037] In some embodiments, the flow rate of the internal coagulation fluid is 1 mL / min-10 mL / min, preferably 3 mL / min-8 mL / min. Exemplary flow rates can be 3 mL / min, 3.5 mL / min, 4 mL / min, 4.5 mL / min, 5 mL / min, 5.5 mL / min, 6 mL / min, 6.5 mL / min, 7 mL / min, 7.5 mL / min, and 8 mL / min, but are not limited thereto.

[0038] Furthermore, the extrusion temperature of the casting solution is 20℃-80℃, more preferably 25℃-60℃; the extrusion temperature of the internal coagulation solution is 18℃-40℃, more preferably 20℃-30℃.

[0039] Optionally, the internal coagulation solution includes, but is not limited to, deionized water, a mixed solution of deionized water and an organic solvent; wherein, the volume fraction of the organic solvent in the mixed solution of deionized water and organic solvent can be 20 vol%-40 vol%, and the organic solvent can be, for example, ethanol, isopropanol, ethylene glycol, acetone, N-methylpyrrolidone, etc.

[0040] Optionally, the temperature in the external coagulation bath is 5℃-30℃, and the residence time in the external coagulation bath is 10s-600s; more preferably, the temperature in the external coagulation bath is 5℃-25℃, and the residence time in the external coagulation bath is 30s-300s. The solvent in the external coagulation bath includes, but is not limited to, deionized water.

[0041] (14) The formed hollow fiber base membrane is washed and then heat-treated; In this step, the formed hollow fiber base membrane is washed to remove residual solvents and other soluble components from the formed hollow fiber base membrane.

[0042] Preferably, the solvent used for washing is deionized water, specifically, the formed hollow fiber base membrane can be immersed in water for washing.

[0043] Furthermore, heat treatment of the formed hollow fiber membrane can promote polymer chain rearrangement and enhance intermolecular forces, thereby improving the membrane's mechanical strength, chemical stability, and antifouling ability, optimizing its pore structure, and improving nanofiltration performance.

[0044] In some specific and preferred embodiments, the heat treatment temperature can be 60℃-100℃ and the time can be 60min-240min. More preferably, the heat treatment temperature can be 70℃-90℃ and the time can be 90min-180min.

[0045] Specifically, step (2) includes; (21) After wetting the hollow fiber base membrane, contact its inner cavity with dopamine buffer solution to allow dopamine to self-oxidize and deposit in the hollow fiber base membrane to form a dopamine layer; In this step, the formed dopamine layer can serve as an intermediate adhesion layer, facilitating the formation of a brush layer on the hollow fiber base membrane. Specifically, a dopamine buffer solution can be introduced into the interior of the fully wetted hollow fiber base membrane, allowing the dopamine buffer solution to undergo an auto-oxidation reaction with the hollow fiber base membrane after extrusion at a preset temperature, thereby depositing a dopamine layer on the surface.

[0046] Further, the dopamine buffer solution is composed of dopamine hydrochloride, tris(hydroxymethyl)aminomethane hydrochloride, and deionized water, wherein the concentration of dopamine hydrochloride is 0.1 g / L-5 g / L, and the pH of the dopamine buffer solution is 7.5-9.5. If the concentration of dopamine hydrochloride in the dopamine buffer solution is too low, insufficient deposition on the inner surface of the membrane will occur, which is detrimental to the stable grafting of subsequent brush layers; if the concentration is too high, it is easy to form an excessively thick or uneven deposition layer, increasing mass transfer resistance and affecting the construction of subsequent functional layers. More preferably, the concentration of dopamine hydrochloride is 0.5 g / L-2 g / L, and the pH of the dopamine buffer solution is 8-9.

[0047] In some specific and preferred embodiments, the preset temperature is 20℃-30℃, and the reaction time is 2h-10h. After the reaction is completed, unbound or weakly adsorbed residual dopamine can be washed away to obtain a hollow fiber membrane with a dopamine intermediate layer uniformly covered on the inner surface. The solvent used for washing includes, but is not limited to, deionized water.

[0048] (22) The material obtained in step (21) is immersed in a mixture containing zwitterionic monomers and hydrophilic polymer monomers, and polymerized under the action of an initiator to form a brush layer.

[0049] In this step, under the influence of the dopamine layer, zwitterionic monomers and hydrophilic polymer monomers can accumulate on the inner surface of the membrane and undergo surface-initiated polymerization under the action of an initiator, thereby constructing a dense polymer brush layer on the surface of the dopamine layer. The resulting brush layer exhibits good surface coverage and grafting stability.

[0050] Understandably, after the reaction is complete, the membrane can be washed to remove unreacted monomers and free polymers, thereby obtaining a hollow fiber nanofiltration membrane with a superhydrophilic antifouling brush layer formed on its inner surface. Preferably, the washing solvent is deionized water.

[0051] Preferably, the total mass fraction of the zwitterionic monomer and the hydrophilic polymer monomer is 1wt%-50wt%; more preferably, it is 5wt%-30wt%.

[0052] Furthermore, in the mixture, the mass ratio of the zwitterionic monomer to the hydrophilic polymer monomer is (1-4):1, which can balance the hydration layer construction ability, brush layer flexibility, and interface stability. If the proportion of zwitterionic monomer is too low, the surface hydration effect is insufficient, and the antifouling effect is not obvious; if the proportion of hydrophilic polymer monomer is too low, the layering and stability of the brush layer are insufficient. Excessive amounts of either component may lead to problems such as excessively thick polymer layers, increased mass transfer resistance, or unstable surface grafting. More preferably, the mass ratio of the zwitterionic monomer to the hydrophilic polymer monomer is (1.5-3):1.

[0053] Furthermore, the polymerization conditions under the action of the initiator include: a pH of 2-10 in the reaction system, an inert gas atmosphere, a reaction temperature of 25℃-80℃, and a reaction time of 0.1h-6h; more preferably, a pH of 4-9 in the reaction system, a reaction temperature of 40℃-70℃, and a reaction time of 0.5h-3h. It is understood that the inert gas atmosphere can include a nitrogen atmosphere, an argon atmosphere, etc.

[0054] Optionally, the zwitterionic monomer is selected from one or more of sulfobetaine methacrylate and carboxybenzaine methacrylate; the hydrophilic polymer monomer is selected from one or more of 2-carboxyethyl methacrylate, polyethylene glycol methacrylate, and acrylamide.

[0055] Optionally, the mixture containing the zwitterionic monomer and the hydrophilic polymer monomer can be an aqueous dispersion containing the zwitterionic monomer and the hydrophilic polymer monomer.

[0056] Optionally, the initiator can be a free radical initiator, such as ammonium persulfate or potassium persulfate, but not limited thereto; the amount of the initiator added is 0.1wt%-6wt% of the total mass of the zwitterionic monomer and the hydrophilic polymer monomer.

[0057] Specifically, step (3) includes; (31) The photocatalytic material, adsorbent material, binder and second solvent are mixed to form a dispersion; In this step, the photocatalytic material and the adsorbent material can be first dispersed in a second solvent according to a preset ratio, and then a binder can be added to form a stable composite dispersion. It is understood that the photocatalytic material and the adsorbent material can be dispersed using ultrasonic dispersion in the second solvent.

[0058] The total dosage and mass ratio of photocatalytic material and adsorbent material need to balance self-cleaning ability, adsorption and enrichment ability, and film deposition stability. Preferably, the total mass fraction of photocatalytic material and adsorbent material in the dispersion is 0.1wt%-5wt%, wherein the mass ratio of photocatalytic material to adsorbent material is 1:(0.5-4). If the amount of photocatalytic material is too small, the self-cleaning effect is not obvious; if the amount of adsorbent material is too small, the enrichment and removal of odor substances and organic pollutants will be insufficient; if either component is too high, it is easy to cause particle agglomeration, excessively thick deposition layer, increased film resistance, and decreased adhesion stability. More preferably, the mass ratio of photocatalytic material to adsorbent material is 1:(0.8-3).

[0059] Furthermore, the photocatalytic material has an average particle size of 10nm-500nm and a specific surface area of ​​5m². 2 / g-200m 2 / g can balance photoresponsiveness, dispersion stability and stable deposition on the film surface.

[0060] Optionally, the photocatalytic material is a visible light responsive photocatalytic material, specifically selected from one or more of graphitic carbon nitride (g-C3N4), bismuth vanadate (BiVO4), and bismuth tungstate (Bi2WO6).

[0061] Furthermore, the pore size of the adsorbent material is 0.5nm-5nm, and the average particle size is 20nm-500nm; it can balance adsorption capacity, mass transfer efficiency, and stable loading on the membrane surface.

[0062] Optionally, the adsorbent material is selected from one or more of β-cyclodextrin / propylene oxide crosslinks (B-CD / propylene oxide crosslinks) and porous aromatic polymers. These adsorbent materials possess good enrichment capacity for small organic molecules and aqueous phase stability, making them suitable for synergistic construction of composite functional layers with photocatalytic materials. The β-cyclodextrin / propylene oxide crosslink is a porous polymer formed by crosslinking β-cyclodextrin and propylene oxide. Exemplary examples of porous aromatic polymers include divinylbenzene-based porous organic polymers, triazine-based porous organic polymers, and polystyrene. Specifically, the divinylbenzene-based porous organic polymer can be a porous aromatic polymer prepared using divinylbenzene as the crosslinking monomer; the polystyrene can be a highly crosslinked polystyrene resin. The adsorbent material can be a commercially available product or synthesized in-house.

[0063] Optionally, the adhesive is one or more of glutaraldehyde, carbodiimide, and polyvinyl alcohol. The use of the adhesive can promote the adhesion of photocatalytic materials and adsorbent materials to the polymer brush layer. The dosage of the adhesive is 0.01wt%-1wt% of the dispersion, preferably 0.01wt%-0.1wt%.

[0064] Optionally, the second solvent is water or an aqueous solution containing ethanol, preferably an aqueous solution containing ethanol, which provides better dispersibility for photocatalytic and adsorbent materials. The volume fraction of ethanol in the aqueous solution is less than 30 vol%; more preferably 0.1 vol%-30 vol%; and even more preferably 5 vol%-20 vol%.

[0065] Optionally, when using ultrasonic dispersion, the ultrasonic power can be adjusted to 50W-500W and the ultrasonic time to 10min-120min; more preferably, the ultrasonic power can be adjusted to 100W-300W and the ultrasonic time to 20min-60min.

[0066] (32) Wet the material obtained in step (2), and use an internal circulation process to bring the dispersion into contact with the brush layer, and deposit a photocatalytic / adsorption composite functional layer on the brush layer; In this step, an internal circulation process is used to circulate and uniformly spray the dispersion onto the brush layer. By continuously circulating the dispersion inside the brush layer, the internal circulation process promotes full contact between the dispersion and the brush layer, and achieves uniform deposition and efficient mass transfer of the dispersion within the brush layer, thereby coating the brush layer with a photocatalytic / adsorption composite functional coating of uniform thickness.

[0067] Furthermore, the circulation temperature of the internal circulation process is 10℃-50℃, the circulation flow rate is 0.5mL / min-10mL / min, and the circulation time is 0.2h-4h. By controlling the circulation temperature and circulation flow rate, the transport rate of active components in the dispersion to the brush surface can be significantly improved, and the deposition behavior of photocatalytic particles and adsorbent particles at the interface can be controlled, inhibiting agglomeration and promoting continuous and uniform deposition of active components on the brush surface. More preferably, the circulation temperature of the internal circulation process is 20℃-35℃, the circulation flow rate is 3mL / min-8mL / min, and the circulation time is 0.5h-2h.

[0068] (33) The material obtained in step (32) is added to a crosslinking agent to carry out a crosslinking reaction, and a photocatalytic / adsorption composite functional layer is formed on the brush layer.

[0069] In this step, the added crosslinking agent can react with the active groups in the coated photocatalytic / adsorption composite functional layer to form a three-dimensional network structure, which promotes the adhesion of the photocatalytic / adsorption composite functional film layer on the brush layer and enhances the density, mechanical strength, and stability of the photocatalytic / adsorption composite functional layer.

[0070] Preferably, the crosslinking reaction time is 5 min to 120 min. The crosslinking agent is one or more of glutaraldehyde and carbodiimides, wherein the carbodiimides include, but are not limited to, dicyclohexylcarbodiimide, diisopropylcarbodiimide, and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride. Understandably, the crosslinking agent is added in solution form, wherein the mass fraction of the crosslinking agent is 0.01 wt% to 2 wt%. In some specific and preferred embodiments, the crosslinking agent can also be circulated through an internal circulation process to promote the crosslinking reaction.

[0071] Furthermore, before adding the crosslinking agent, the material obtained in step (32) can be heat-dried to promote solvent evaporation and promote the crystallization of photocatalytic materials and adsorbent materials, thus providing conditions for the crosslinking reaction.

[0072] Optionally, the heat drying temperature is 30℃-80℃, and the time is 10min-240min. If the temperature is too low, crystallization will be insufficient, resulting in a loose film layer. If the temperature is too high, it will hinder the cross-linking reaction and may even lead to degradation of the polymer material. More preferably, the heat drying temperature is 40℃-70℃, and the time is 30min-120min.

[0073] In some embodiments, step (3) further includes (34) heat-treating the material obtained in step (33) to obtain a hollow fiber nanofiltration membrane with a photocatalytic / adsorption composite functional layer.

[0074] Preferably, the heat treatment temperature is 30℃-80℃ and the time is 0.5h-4h, which can effectively remove unfixed particles and residues; more preferably, the heat treatment temperature is 40℃-70℃ and the time is 1h-3h.

[0075] Accordingly, the present invention also provides a hollow fiber nanofiltration membrane, which is prepared by the above preparation method.

[0076] Accordingly, the present invention also provides an application of hollow fiber nanofiltration membrane for the deep treatment of drinking water, municipal water or sewage. The membrane specific flux changes significantly and gradually over time, which can effectively inhibit the irreversible deposition of organic pollutants on the membrane surface. Moreover, it has excellent in-situ self-cleaning and flux self-recovery capabilities, and has high removal efficiency for odor substances containing geosmin (GSM) and 2-methylisoborneol (2-MIB).

[0077] The present invention will be further described below with reference to specific embodiments: Example 1 This embodiment provides a hollow fiber nanofiltration membrane, the preparation method of which is as follows: S1. Weigh 14g of polyethersulfone, 4g of sulfonated polyethersulfone, 2g of polyvinylpyrrolidone, and 0.5g of lithium chloride and add them to 79.5g of N-methylpyrrolidone. Stir mechanically at 60℃ for 8 hours until completely dissolved to obtain 100g of homogeneous casting solution. Place the casting solution in a sealed container and put it in a vacuum drying oven. Degas under reduced pressure at 40℃ and -0.08MPa for 12 hours, then age at 40℃ for 12 hours. Filter through a 0.45μm filter membrane to obtain a homogeneous casting solution. The filtered casting solution was placed in the outer barrel of the hollow fiber spinning device and kept at a constant temperature of 35°C. An N-methylpyrrolidone mixed solution with a volume fraction of approximately 30% was introduced into the inner channel as the inner coagulation solution and maintained at 25°C. The flow rate of the casting solution was set to 10 mL / min, and the flow rate of the inner coagulation solution was set to 5 mL / min, allowing both to be extruded promptly through the outer and inner channels of the spinneret. After passing through an air gap of approximately 10 cm, the solution entered a 10 L deionized water external coagulation bath at 25°C to complete the wet phase inversion. The residence time in the external coagulation bath was no less than 300 s before winding and collecting to obtain the hollow fiber primary membrane. The obtained hollow fiber primary membrane was then immersed in deionized water for 24 h, followed by heat treatment at 80°C for 120 min, and cooled to room temperature to obtain a hydrophilic, negatively charged polyethersulfone / sulfonated polyethersulfone hollow fiber base membrane.

[0078] S2. First, wet the polyethersulfone / sulfonated polyethersulfone hollow fiber membrane obtained in S1 with deionized water; then prepare a dopamine alkaline buffer solution: weigh 0.1g of dopamine hydrochloride and 1.2g of tris(hydroxymethyl)aminomethane hydrochloride, add deionized water to make up to 100mL, adjust the pH to 8.5 with sodium hydroxide, and then pour it into a 250mL beaker. Use a peristaltic pump to circulate the solution into the hollow fiber membrane from the inner cavity of the hollow fiber at a flow rate of 5mL / min. React at 25℃ for 4h to allow dopamine to self-oxidize and deposit on the inner surface of the membrane to form an adhesive intermediate layer. Subsequently, continue to use deionized water to remove dopamine residue, and obtain a hollow fiber membrane with a uniform dopamine intermediate layer on the inner surface. Subsequently, a mixture containing zwitterionic monomers and hydrophilic polymer monomers was prepared: 10g of sulfobetaine methacrylate, 5g of polyethylene glycol methacrylate, and deionized water were added to a 250mL beaker and stirred to dissolve. Then, 0.3g of ammonium persulfate was weighed and added to the monomer solution, and the pH was adjusted to 7. After deoxygenation by bubbling under nitrogen for 30 minutes, the hollow fiber membrane bundle with a dopamine interlayer was immersed in the monomer / initiator and reacted in an oil bath at 60℃ for 2 hours to construct a dense zwitterionic / hydrophilic copolymer brush layer. After the reaction was completed, the hollow fiber base membrane was removed from the reaction solution, and unreacted monomers and free polymers were immediately removed with deionized water to finally obtain a hollow fiber nanofiltration membrane with a superhydrophilic antifouling brush layer on the inner surface.

[0079] S3. Prepare a photocatalytic / adsorption composite dispersion. Weigh 0.5g of visible light-responsive photocatalyst graphitic carbon nitride (g-C3N4) powder and 0.5g of organic adsorbent β-cyclodextrin-propylene oxide crosslinked polymer into a beaker. Add 100mL of deionized water, followed by 0.02g of polyvinyl alcohol as a binder. Disperse using ultrasound for 30min to obtain a g-C3N4 / β-cyclodextrin composite dispersion. Load the hollow fiber nanofiltration membrane obtained in S2 into a small shell-and-tube membrane module. Connect the composite dispersion to the inlet of the membrane module and circulate it from the inner cavity at a flow rate of 5mL / min using a peristaltic pump at 25℃ for 60min, so that the photocatalytic powder and adsorbent particles are uniformly deposited on the antifouling brush layer on the inner surface. After spraying, switch directly to 0.5wt% glutaraldehyde aqueous solution and circulate it from the inner cavity of the membrane at a flow rate of 5mL / min. Crosslinking treatment is carried out at 40℃ for 60min. After crosslinking, deionized water is used to remove the unfixed components on its surface, and an in-situ clean and anti-fouling hollow fiber nanofiltration membrane with a photocatalytic / adsorption composite functional layer on the inner surface can be obtained.

[0080] Example 2 This embodiment provides a hollow fiber nanofiltration membrane, which is basically the same as that in Embodiment 1, except that: S1. Adjust the ratio of polyethersulfone to sulfonated polyethersulfone. Specifically: Weigh 12g of polyethersulfone, 8g of sulfonated polyethersulfone, 2g of polyvinylpyrrolidone and 0.5g of lithium chloride and add them to 77.5g of N-methylpyrrolidone.

[0081] S2. Adjust the ratio of sulfo-beet methacrylate, polyethylene glycol methacrylate, and ammonium persulfate. Specifically: Weigh out 12g of sulfobetaine methacrylate, 6g of polyethylene glycol methacrylate and 0.36g of ammonium persulfate, and adjust the pH to 7.5.

[0082] The remaining steps are the same as in Example 1.

[0083] Example 3 This embodiment provides a hollow fiber nanofiltration membrane, which is basically the same as that in Embodiment 1, except that step S3 is adjusted. Specifically: S3: First, prepare the photocatalytic / adsorption composite dispersion. Weigh 0.3g of visible light-responsive photocatalyst bismuth vanadate (BiVO4) nanoparticles and 0.7g of organic adsorbent divinylbenzene crosslinked porous aromatic polymer (POP) into a beaker, pre-disperse in 100mL of deionized water, then add 0.02g of polyvinyl alcohol as a binder, and continue ultrasonic dispersion for 30min to obtain the BiVO4 / POP composite dispersion. Load the hollow fiber nanofiltration membrane obtained in S2 into a small shell-and-tube membrane module. Connect the BiVO4 / POP composite dispersion to the membrane module inlet, and circulate it from the inner cavity at a flow rate of 8mL / min using a peristaltic pump at 25℃ for 45min, allowing the photocatalytic powder and organic adsorbent particles to be uniformly deposited on the antifouling brush layer on the inner surface. After spraying, directly switch to a 0.2wt% water-soluble carbodiimide aqueous solution, circulate it from the inner cavity of the membrane at a flow rate of 5mL / min, and perform crosslinking treatment at 30℃ for 30min. After cross-linking, the unparticipated substances on the surface are removed with deionized water to obtain an in-situ clean and anti-fouling hollow fiber nanofiltration membrane with a BiVO4 / POP photocatalytic / adsorption composite functional layer on the inner surface.

[0084] Comparative Example 1 This comparative example provides a hollow fiber nanofiltration membrane, the preparation method of which is basically the same as that of Example 1, except that: The casting solution in step S1 does not include sulfonated polyethersulfone and hydrophilic additives, nor does it include steps S2 and S3 from Example 1. Specifically: 18g of polyethersulfone and 0.5g of lithium chloride were weighed and added to 81.5g of N-methylpyrrolidone. The mixture was mechanically stirred at 60℃ for 8 hours until completely dissolved, yielding 100g of homogeneous casting solution. The casting solution was placed in a sealed container and then placed in a vacuum drying oven. It was degassed under reduced pressure at 40℃ and -0.08MPa for 12 hours, followed by aging at 40℃ for 12 hours. The resulting homogeneous casting solution was then filtered through a 0.45μm filter membrane. The filtered casting solution was placed in the outer barrel of a hollow fiber spinning device and kept at a constant temperature of 35°C. An N-methylpyrrolidone mixed solution with a volume fraction of approximately 30% was introduced into the inner channel as the inner coagulation solution and maintained at 25°C. The casting solution flow rate was set to 10 mL / min and the inner coagulation solution flow rate to 5 mL / min, allowing both to be extruded promptly through the outer and inner channels of the spinneret. After passing through an air gap of approximately 10 cm, the solution entered a 10 L deionized water external coagulation bath at 25°C to complete the wet phase inversion. The residence time in the external coagulation bath was no less than 300 s before winding and collecting to obtain the hollow fiber primary membrane. The obtained primary membrane was then immersed in deionized water for 24 h, followed by heat treatment at 80°C for 120 min, and then cooled to room temperature to obtain a hydrophilic, negatively charged polyethersulfone / sulfonated polyethersulfone hollow fiber base membrane.

[0085] Comparative Example 2 This comparative example provides a hollow fiber nanofiltration membrane, the preparation method of which is basically the same as that of Example 1, except that: Steps S2 and S3 in Example 1 are not included.

[0086] Comparative Example 3 This comparative example provides a hollow fiber nanofiltration membrane, the preparation method of which is as follows: S1, the same as S1 in Example 1; S2. First, wet the polyethersulfone / sulfonated polyethersulfone hollow fiber membrane obtained in S1 with deionized water; then prepare a dopamine alkaline buffer solution: weigh 0.1g of dopamine hydrochloride and 1.2g of tris(hydroxymethyl)aminomethane hydrochloride, add deionized water to make up to 100mL, adjust the pH to 8.5 with sodium hydroxide, and then pour it into a 250mL beaker. Use a peristaltic pump to circulate the solution into the hollow fiber membrane from the inner cavity of the hollow fiber at a flow rate of 5mL / min. React at 25℃ for 4h to allow dopamine to self-oxidize and deposit on the inner surface of the membrane to form an adhesive intermediate layer. Subsequently, continue to use deionized water to remove dopamine residue, and obtain a hollow fiber membrane with a uniform dopamine intermediate layer on the inner surface.

[0087] Comparative Example 4 This comparative example provides a hollow fiber nanofiltration membrane, the preparation method of which is basically the same as that of Example 1, except that: Step S3 in Example 1 is not included.

[0088] Comparative Example 5 This comparative example provides a hollow fiber nanofiltration membrane, the preparation method of which is as follows: S1, the same as S1 in Example 1; S2. First, wet the polyethersulfone / sulfonated polyethersulfone hollow fiber membrane obtained in S1 with deionized water; then prepare a dopamine alkaline buffer solution: weigh 0.1g of dopamine hydrochloride and 1.2g of tris(hydroxymethyl)aminomethane hydrochloride, add deionized water to make up to 100mL, adjust the pH to 8.5 with sodium hydroxide, and then pour it into a 250mL beaker. Use a peristaltic pump to circulate the solution into the hollow fiber membrane from the inner cavity of the hollow fiber at a flow rate of 5mL / min. React at 25℃ for 4h to allow dopamine to self-oxidize and deposit on the inner surface of the membrane to form an adhesive intermediate layer. Subsequently, continue to use deionized water to remove dopamine residue, and obtain a hollow fiber membrane with a uniform dopamine intermediate layer on the inner surface; S3, the same as S3 in Example 1, involves fixing a photocatalyst and an adsorbent on the inner surface of the base film where the dopamine layer is formed, to form a photocatalytic / adsorption composite functional layer.

[0089] Performance testing 1. Morphology Test: The appearance of the hollow fiber nanofiltration membrane obtained in Example 1 was recorded, and its inner surface and cross-section were scanned using SEM. The results are as follows: Figures 1-3 As shown.

[0090] Figure 1 A photograph of the obtained hollow fiber nanofiltration membrane; Figure 2 The image shows the SEM image of the inner surface of the hollow fiber nanofiltration membrane. It can be seen that the inner surface of the membrane is relatively flat, with only a small number of fine particles distributed. No obvious defects, pores or large areas of looseness are observed, indicating that a relatively continuous and uniform surface coating layer has been formed on the inner surface of the membrane after modification. Figure 3 The SEM image of the hollow fiber nanofiltration membrane cross-section reveals a relatively uniform membrane wall thickness and a relatively dense selective layer on the inner surface, beneath which lies a support structure combining finger-like pores and sponge-like micropores. These morphological characteristics indicate that the prepared membrane possesses a relatively complete separation layer and a multi-level porous support layer structure, which is beneficial for ensuring both membrane integrity and mechanical stability while maintaining separation and mass transfer performance.

[0091] 2. A simulated water sample was prepared using deionized water containing 10 mM NaCl, 50 mg / L humic acid, and a pH of approximately 7. The sample was kept at a constant temperature of 25°C and an inlet pressure of approximately 0.45 MPa for 24 hours without chemical cleaning. The specific flux trends of the hollow fiber nanofiltration membranes obtained in Examples 1-3 and Comparative Examples 1-5 were investigated.

[0092] Where, membrane specific flux = J r / J0×100%; where J is the formula. r J0 is the real-time membrane flux, and J0 is the initial membrane flux.

[0093] Test results are as follows Figure 4 As shown.

[0094] like Figure 4 As shown, under the same influent water quality and operating conditions, the membrane specific flux of Comparative Examples 1-5 decreased rapidly with operating time. Comparative Examples 1 and 2 showed a significant decrease in flux within a short period, with the specific flux of Comparative Example 1 dropping to 0.5 after 24 hours. Although the flux decline in Comparative Examples 3 and 4 was somewhat mitigated by simple hydrophilic or brush layer modification, it still showed a continuous downward trend. Although Comparative Example 5 introduced a photocatalytic / adsorption composite functional layer, its flux retention capacity remained limited due to the lack of a stable antifouling interface structure. In contrast, the membrane specific flux of Examples 1-3 changed more gradually over time, remaining at a high level after 24 hours of operation. This indicates that the interface structure synergistically constructed by the polyethersulfone / sulfonated polyethersulfone base membrane, dopamine layer, and zwitterionic / hydrophilic brush layer in this invention can effectively inhibit the irreversible deposition of organic pollutants on the membrane surface.

[0095] 3. Use deionized water to prepare a water body containing 10mM NaCl, 50mg / L humic acid, and a pH of about 7 as a simulated water sample. Under the operating conditions of 25℃ and inlet water pressure of about 0.45MPa, run continuously for 24 hours and then perform light self-cleaning as one cycle to investigate the trend of membrane specific flux recovery rate of hollow fiber nanofiltration membranes obtained in Examples 1-3 and Comparative Examples 1-5.

[0096] Wherein, membrane specific flux recovery rate = J b / J0×100%; where J0 is the membrane flux before cleaning, J b This represents the membrane flux after cleaning.

[0097] Test results are as follows Figure 5 As shown.

[0098] from Figure 5 It can be seen that after four cleaning cycles, the flux recovery rates of Comparative Examples 1-5 were generally low and gradually decreased with the number of cycles, while the flux recovery rates of Examples 1-3 remained at a high level with minimal attenuation. This indicates that the hollow fiber nanofiltration membrane in this invention has excellent in-situ self-cleaning and flux self-recovery capabilities under visible light, achieving stable anti-fouling performance under long-term operating conditions.

[0099] 4. Using ultrapure water to prepare a mixed solution of 500 ng / L geosmin (GSM) and 2-methylisoborneol (2-MIB) as the membrane inlet water, the removal performance of hollow fiber nanofiltration membranes obtained in Examples 1-3 and Comparative Examples 1-5 for typical odor substances was investigated.

[0100] The contents of GSM and 2-MIB in the water before and after treatment were determined using a gas chromatography / mass spectrometry system (Agilent 7890A-5975C), and the removal rate was calculated.

[0101] Wherein, removal rate = (A-A0) / A×100%; where A is the concentration of the analyte before the membrane (ng / L) and A0 is the concentration of the analyte after the membrane (ng / L).

[0102] Test results are as follows Figure 6 As shown.

[0103] As shown in the figure, Examples 1-3 all exhibited significantly better removal effects on GSM and 2-MIB than Comparative Examples 1-5. Examples 1 and 3 consistently maintained removal rates of over 95% for both odor-causing substances, while Example 2 showed further improvement, with GSM removal approaching 100% and 2-MIB removal nearing complete removal. In contrast, Comparative Examples 1-3, being unmodified or partially modified hollow fiber nanofiltration membranes, generally exhibited lower removal rates for GSM and 2-MIB, only partially at the levels of the Examples. Although Comparative Examples 4 and 5 introduced hydrophilic brush layers or photocatalytic / adsorption particle layers, their incomplete interface structures resulted in only moderate odor-causing substance removal rates, significantly lower than Examples 1-3. In summary, this invention, by synergistically constructing a superhydrophilic antifouling brush layer and a photocatalytic / adsorption composite functional layer on the inner surface of hollow fibers, improves the removal efficiency of hollow fiber nanofiltration membranes for GSM and 2-MIB, making it suitable for deep purification of municipal water sources containing odor-causing substances.

[0104] The above description is merely a preferred embodiment of the present invention and should not be construed as limiting the scope of the invention. Therefore, any equivalent variations made in accordance with the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for preparing a hollow fiber nanofiltration membrane, characterized in that, Includes the following steps: (1) A casting solution was prepared by mixing polyethersulfone, sulfonated polyethersulfone, hydrophilic additives and a first solvent, and then a hollow fiber base membrane was obtained by phase inversion method; (2) A dopamine layer is constructed in the inner cavity of the hollow fiber base membrane, and a zwitterion and hydrophilic polymer are grafted through a polymerization reaction to form a brush layer; (3) Fix photocatalytic material and adsorbent material on the brush layer to form a photocatalytic / adsorption composite functional layer, thereby obtaining the hollow fiber nanofiltration membrane; Step (2) specifically includes: (21) After wetting the hollow fiber base membrane, contact its inner cavity with dopamine buffer solution to allow dopamine to self-oxidize and deposit in the hollow fiber base membrane to form a dopamine layer; (22) The material obtained in step (21) is immersed in a mixture containing zwitterionic monomers and hydrophilic polymer monomers, and polymerized under the action of an initiator to form a brush layer; Step (3) specifically includes: (31) The photocatalytic material, adsorbent material, binder and second solvent are mixed to form a dispersion; (32) Wet the material obtained in step (2), and use an internal circulation process to bring the dispersion into contact with the brush layer, and deposit photocatalytic material and adsorbent material on the brush layer; (33) The material obtained in step (32) is added to a crosslinking agent to carry out a crosslinking reaction, and a photocatalytic / adsorption composite functional layer is formed on the brush layer; The zwitterionic monomer is selected from one or more of sulfobetaine methacrylate and carboxybetaine methacrylate; the hydrophilic polymer monomer is selected from one or more of 2-carboxyethyl methacrylate, polyethylene glycol methacrylate, and acrylamide. The photocatalytic material is selected from one or more of g-C3N4, BiVO4, and Bi2WO6; The adsorbent material is selected from porous aromatic polymers.

2. The method for preparing the hollow fiber nanofiltration membrane as described in claim 1, characterized in that, In step (1), the total solid content of polyethersulfone and sulfonated polyethersulfone in the casting solution is 10wt%-35wt%, wherein the sulfonated polyethersulfone is 5wt%-40wt% of the total mass of polyethersulfone and sulfonated polyethersulfone.

3. The method for preparing the hollow fiber nanofiltration membrane as described in claim 1, characterized in that, In step (1), the amount of the hydrophilic additive added is 1wt%-15wt% of the first solvent; The hydrophilic additive is selected from one or more of polyethylene glycol, polyvinyl alcohol, and polyvinylpyrrolidone; The casting solution also includes a pore-forming agent, and the dosage of the pore-forming agent is 0-5 wt% of the casting solution. The pore-forming agent is selected from one or more of calcium chloride, lithium chloride, and lithium carbonate.

4. The method for preparing the hollow fiber nanofiltration membrane as described in claim 1, characterized in that, The total mass fraction of zwitterionic monomers and hydrophilic polymer monomers added to the mixture is 1wt%-50wt%. The mass ratio of the zwitterionic monomer to the hydrophilic polymer monomer is (1-4):

1.

5. The method for preparing the hollow fiber nanofiltration membrane as described in claim 1, characterized in that, In step (31), the total mass fraction of photocatalytic material and adsorbent material in the dispersion is 0.1wt%-5wt%, wherein the mass ratio of the added photocatalytic material and adsorbent material is 1:(0.5-4). The second solvent is water or an aqueous solution containing ethanol; The adhesive is selected from one or more of glutaraldehyde, carbodiimide, and polyvinyl alcohol; the dosage of the adhesive is 0.01wt%-1wt% of the dispersion. In step (32), the circulation temperature of the internal cavity circulation process is 10℃-50℃, and the circulation flow rate is 0.5mL / min-10mL / min; In step (33), the crosslinking agent is one or more of glutaraldehyde and carbodiimide; the crosslinking reaction time is 5 min to 120 min; the crosslinking agent is added in solution form; and the mass fraction of the crosslinking agent is 0.01 wt% to 2 wt%.

6. The method for preparing the hollow fiber nanofiltration membrane as described in claim 1, characterized in that, In step (3), the average particle size of the photocatalytic material is 10nm-500nm, and the specific surface area is 5m². 2 / g-200m 2 / g; The pore size of the adsorbent material is 0.5nm-5nm, and the average particle size is 20nm-500nm.

7. A hollow fiber nanofiltration membrane, characterized in that, It is prepared according to any one of claims 1-6.

8. An application of the hollow fiber nanofiltration membrane as described in claim 7, characterized in that, Used for the deep treatment of municipal water or sewage.

Citation Information

Patent Citations

  • External pressure type hollow fiber industrial nanofiltration membrane and preparation method thereof

    CN111282455A

  • Hydrophilic modified polyethylene film as well as preparation method and application thereof

    CN120001225A

  • Composite membrane with functions of adsorption separation and catalytic degradation of new pollutants as well as preparation method and application of composite membrane

    CN121911246A